Confirmatory Factor Analysis of Understanding Fiqh al-Muwāzanāt and Emotional Maturity in Religious Conflict Resolution - Rahmadi, M. Agung; Said Agil Husin Al-Munawar; Nasution, Helsa; Mawar, Luthfiah; Sihombing, Nurzahara; Lubis, Ismail Saleh (Al-Wasatiyah: Journal of Religious Moderation, 2025)
This study uses a confirmatory factor analysis approach to explore the relationship between understanding fiqh al-muwāzanāt and emotional maturity in religious conflict resolution. Data was collected via an online survey involving 412 respondents (56.3% male; 43.7% female). The model testing results using Structural Equation Modeling (SEM) demonstrated a strong model fit (χ² = 187.24, df = 76, p < 0.001, CFI = 0.942, TLI = 0.927, RMSEA = 0.058, SRMR = 0.043). Furthermore, the findings revealed a significant correlation between the understanding of fiqh al-muwāzanāt and emotional maturity (r = 0.68, p < 0.001), with both variables simultaneously exerting a substantial influence on individuals' ability to resolve religious conflicts (β = 0.42 and β = 0.37, p < 0.001). The mediation analysis results further indicated that emotional maturity mediates the relationship between fiqh al-muwāzanāt understanding and religious conflict resolution (indirect effect = 0.25, 95% CI [0.18, 0.32]). Thus, this study highlights the dynamic interaction between textual religious understanding and individuals' emotional regulation competencies, thereby expanding upon previous studies by Lattu and Schmidt et al., which primarily focused on the cognitive aspects of religious comprehension. Additionally, unlike Najib's study, which relied on a qualitative approach, this research provides empirical evidence through a quantitative-based validation of a more comprehensive theoretical model. Consequently, these findings underscore the urgency of integrating contextual religious understanding and emotional matrity as a strategic intervention approach for resolving religious conflicts in the digital era.